(untitled) (Progressive Agriculture, 2018)
Soil salinity is considered as one of the greatest threats for rice production. Genetic variability analysis of morphological traits related to salt injury is mandatory, which could be helpful in the development of an appropriate breeding program for the selection of salt tolerant rice genotypes from the existing germplasm towards developing new salt tolerant rice varieties. Therefore, the present study has been aimed to evaluate the genetic variability parameters for fourteen morphological traits in thirty local and high yielding rice genotypes using hydroponic culture. Among the rice genotypes under study, Boilam, Nonabokri, Gunshi, Motabamonkhir showed the best performance regarding the morphological traits under different saline conditions (6 dSm -1 and 10 dS m-1). The PCV values were greater than the GCV values for all studied traits indicating the greater environmental influence on the traits. The highest percentage of GCV and PCV were observed in root dry weight, while the lowest were exhibited in main axis diameter. To assist the breeding program, along with variability, estimation of heritability and genetic advance has also been done. High heritability ranging from 80.24% to 94.66% was found among the traits. The genetic advance was highest for survival rate and the lowest was in root dry weight. Eventually, the results indicated the presence of high genetic variability, along with high heritability and genetic advance among genotypes and studied traits, which could provide further insight towards selection of parents for the development of salt tolerant rice varieties. Progressive Agriculture 28 (4): 262-270, 2017